Farmhand (2018), volume 1 ebook Reap what was sown. - Guillory, Rob (Farmhand (2018), 2019)
Jedidiah Jenkins is a simple farmer. But his cash crop isn't corn or soy. He grows fast-healing, highly-customizable human organs. For years, Jed's organic transplants have brought healing to many, but deep in the soil of the Jenkins Family Farm something sinister has taken root. Today this dark seed will begin to sprout, and the Jenkins family will be the first to taste its bitter fruit. Collects FARMHAND #1-5. Author: Rob Guillory. Illustrator: Rob Guillory, Taylor Wells . 2019 Rob Guillory.